Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376174
|View full text |Cite
|
Sign up to set email alerts
|

"No powers, man!": A Student Perspective on Designing University Smart Building Interactions

Abstract: Smart buildings offer an opportunity for better performance and enhanced experience by contextualising services and interactions to the needs and practices of occupants. Yet, this vision is limited by established approaches to building management, delivered top-down through professional facilities management teams, opening up an interaction-gap between occupants and the spaces they inhabit. To address the challenge of how smart buildings might be more inclusively managed, we present the results of a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This highlights the critical need for a holistic approach that involves building occupants in data-driven decision-making processes. It is imperative to bridge the gap between technological advancements, expert insights, and the diverse needs of building occupants for a harmonized and energy-efficient built environment [12].…”
Section: Challenges and Opportunities In Integrating Building Occupan...mentioning
confidence: 99%
“…This highlights the critical need for a holistic approach that involves building occupants in data-driven decision-making processes. It is imperative to bridge the gap between technological advancements, expert insights, and the diverse needs of building occupants for a harmonized and energy-efficient built environment [12].…”
Section: Challenges and Opportunities In Integrating Building Occupan...mentioning
confidence: 99%
“…These works [60,113,117,169] emphasised that granting full agency and autonomy might leave people to pose risks to their own physical or digital safety, and suggest a need to balance these values. Finally, 20 papers suggested that user autonomy and agency contribute to desirable practical outcomes in tasks and activities [e.g., 33,41,120,148], such as increased feelings of responsibility [35], or trust within organisations [177].…”
Section: Independence or Interdependencementioning
confidence: 99%
“…Hence, recent studies have focused on this interaction to improve or facilitate the lives of smart building occupants [17]. In particular, Finnigan and Clear have analyzed how student occupants experienced spaces, how they evaluate them, and how building management might improve considering the occupants [18]. Their case study was based on a smart university building in the UK equipped with a BMS.…”
Section: Human-building Interactionmentioning
confidence: 99%